Pathophysiology and management of liver cirrhosis: from portal hypertension to acute-on-chronic liver failure - Rakesh Kumar Jagdish; Akash Roy; Karan Kumar; Madhumita Premkumar; Mithun Sharma; Padaki Nagaraja Rao; Duvvur Nageshwar Reddy; Anand V. Kulkarni (Frontiers in Medicine, 2023)
Cirrhosis transcends various progressive stages from compensation to decompensation driven by the severity of portal hypertension. The downstream effect of increasing portal hypertension severity leads to various pathophysiological pathways, which result in the cardinal complications of cirrhosis, including ascites, variceal hemorrhage, and hepatic encephalopathy. Additionally, the severity of portal hypertension is the central driver for further advanced complications of hyperdynamic circulation, hepatorenal syndrome, and cirrhotic cardiomyopathy. The management of these individual complications has specific nuances which have undergone significant developments. In contrast to the classical natural history of cirrhosis and its complications which follows an insidious trajectory, acute-on-chronic failure (ACLF) leads to a rapidly downhill course with high short-term mortality unless intervened at the early stages. The management of ACLF involves specific interventions, which have quickly evolved in recent years. In this review, we focus on complications of portal hypertension and delve into an approach toward ACLF.